2021
DOI: 10.3389/fphys.2020.616866
|View full text |Cite
|
Sign up to set email alerts
|

M/M/Infinity Birth-Death Processes – A Quantitative Representational Framework to Summarize and Explain Phase Singularity and Wavelet Dynamics in Atrial Fibrillation

Abstract: RationaleA quantitative framework to summarize and explain the quasi-stationary population dynamics of unstable phase singularities (PS) and wavelets in human atrial fibrillation (AF) is at present lacking. Building on recent evidence showing that the formation and destruction of PS and wavelets in AF can be represented as renewal processes, we sought to establish such a quantitative framework, which could also potentially provide insight into the mechanisms of spontaneous AF termination.ObjectivesHere, we hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(54 citation statements)
references
References 33 publications
3
51
0
Order By: Relevance
“…[ 52 ] In both examples, consistent with our data (Figure 2), an exponential distribution of PS lifetimes and rotors can be seen. [ 17 , 18 ] This is consistent with the notion of quasi-stationary decay dynamics of unstable re-entrant circuits. PersAF = persistent AF.…”
Section: Rationale For Focusing On Phase Singularitiessupporting
confidence: 86%
See 2 more Smart Citations
“…[ 52 ] In both examples, consistent with our data (Figure 2), an exponential distribution of PS lifetimes and rotors can be seen. [ 17 , 18 ] This is consistent with the notion of quasi-stationary decay dynamics of unstable re-entrant circuits. PersAF = persistent AF.…”
Section: Rationale For Focusing On Phase Singularitiessupporting
confidence: 86%
“…This has recently been examined by consideration of the autocorrelation of PS interval series, which converge to zero in the case of non-zero interval lags. [ 55 ]…”
Section: Rationale For a Renewal Theory Approach In Afmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our group has recently proposed a novel technique to quantify fibrillatory dynamics in patients with AF 152,153 . We demonstrated that the RA inter‐formation times, RA inter‐destruction times and lifetimes of RA in animal models and human models with persistent AF follow an exponential distribution, consistent with an underlying renewal process 152 .…”
Section: Future Research: Characterization Of Af Through Their Electro Phenotypementioning
confidence: 70%
“…An issue that is not fully resolved is whether basket‐type catheters may be effective in the mapping of PSs. While in general, it has been suggested that basket catheters may have the theoretical risk of false detection of PSs, we have recently shown that rate constants of PS formation and destruction detected by basket catheters can accurately predict the number and population distribution of observed PS, in line with a property of scale invariance under transformation 47 . This issue would therefore be considered as under debate in the literature at the current time.…”
Section: Discussionmentioning
confidence: 85%